Two-parameter kinematic theory for punching shear in reinforced concrete slabs without shear reinforcement. (15th November 2018) - Kueres, Dominik; Hegger, Josef
Highlights: Development of a kinematic theory considering both flexural and translational deformations (two degrees of freedom). Calculation of shear contributions along the failure crack based on slab deformations. Validation of the kinematic theory by means of systematic punching test series and databanks. Discussion of differences between punching shear behavior of slender and compact slabs. Abstract: Measurements taken from recent test series with varying slenderness reveal strong differences between fracture kinematics of slender and compact slabs failing in punching. In accordance with the assumptions of the existing kinematic punching shear resistance models, the deformation behavior of slender slabs is governed by flexural deformations. However, in very compact slabs only small flexural deformations occur and the deformation behavior is dominated by translational deformations. In the transition region between slender and very compact slabs, the deformation behavior is influenced by both deformation components. As a consequence, the general application of the existing kinematic models to both slender and compact slabs might yield unexpected results. In this paper, a two-parameter kinematic theory for punching shear in reinforced concrete slabs without shear reinforcement is developed taking into account the aforementioned observations. In the theory, it is assumed that shear forces are transmitted along the failure crack by four shear contributions, namely the contributions of compression ring, aggregate interlock, residual tensile stresses, and dowel action. The magnitude of shear contributions is estimated based on the deformed slab accounting for two degrees of freedom (DOFs). While the first DOF accounts for flexural deformations, the second DOF considers translational deformations. Subsequently, the punching strength is calculated by summation of the contributions. The evaluation of the proposed theory by means of systematic test series and databanks yields good agreement between predictions and experimental results. Especially, the differences between flat slabs and column bases can be explained in a consistent manner by the theory.